Regenerative Electrocatalytic Redox Cycle of Copper Sulfide for Sustainable NH3 Production under Ambient Conditions - Kim, Hee Soo; Choi, Jihyun; Kong, Jimin; Kim, Hansung; Yoo, Sung Jong; Park, Hyun S. (AMER CHEMICAL SOC, 2021)
Electrochemical nitrogen reduction reaction (NRR) is a promising method for energy-efficient and low-emission NH3 production. Herein, we report electrochemical NH3 production using a copper sulfide-based electrocatalyst. A solid-state synthesis is employed to prepare the Cu9S5 catalyst for artificial N-2 fixation in a neutral aqueous electrolyte. Despite an excellent NRR activity of 10.8 +/- 0.4 mu g/hcm(2) at -0.5 V-RHE, however, the catalyst itself is reductively degraded during the NRR. To achieve continuous electrochemical NH3 production, a regenerative electrochemical sulfur cycle is introduced that revives the Cu9S5 crystal structure and NRR activities. The electrochemical regeneration process reconstructing the metal-sulfur bond in between sequential NH3 production processes restores the NRR activity. Importantly, catalytic surfaces providing a labile sulfhydryl functional group attached to the N-2-adsorption metal center are required to achieve efficient NRR activity under ambient conditions.
Keywords: CARBON SPHERES; UNS N08800; NITROGEN; CUS; REDUCTION; TEMPERATURE; NANOSHEETS; AMMONIA; N-2; NANOPARTICLES